2008
DOI: 10.2351/1.2995762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nd:Yttrium-aluminum-garnet laser radiation on Ti6Al4V alloy properties for biomedical applications

Abstract: In situ strain profiling of elastoplastic bending in Ti-6Al-4V alloy by synchrotron energy dispersive x-ray diffractionThe effect of Nd:yttrium-aluminum-garnet laser on the microtopography and physicochemical properties of Ti6Al4V alloy are investigated in the view of biomedical applications. The surface roughness and hardness for laser treated samples ͑LTS͒ at 140 J cm −2 were measured 7 Ϯ 0.02 and 825 vickers hardness number, respectively. This superior microhardness value is attributed to grain refinement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…From micro-mechanical point of view, the previous finding of enhanced properties [16,20,22] after laser treatment at 140 Jcm -2 compared to untreated, as well as 70 and 250 Jcm -2 samples, were consistent with new finding of significant difference between samples' surface morphologies. The higher surface hardness (850, 377 HVN for 140 Jcm -2 and untreated samples, respectively), enhanced corrosion resistance, lower contact angle (35°for 140 Jcm -2 and 70°for untreated sample) and higher surface tension (60 mNm -1 ) for 140 Jcm -2 compared to untreated surface (39 mNm -1 ) have been reported before.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From micro-mechanical point of view, the previous finding of enhanced properties [16,20,22] after laser treatment at 140 Jcm -2 compared to untreated, as well as 70 and 250 Jcm -2 samples, were consistent with new finding of significant difference between samples' surface morphologies. The higher surface hardness (850, 377 HVN for 140 Jcm -2 and untreated samples, respectively), enhanced corrosion resistance, lower contact angle (35°for 140 Jcm -2 and 70°for untreated sample) and higher surface tension (60 mNm -1 ) for 140 Jcm -2 compared to untreated surface (39 mNm -1 ) have been reported before.…”
Section: Discussionsupporting
confidence: 86%
“…Upon selecting non-appropriate surface properties, formation of a fibrous tissue layer between implant and bone negatively affect bone formation results in eventual loosening of implant [14]. Local hardening and improvement of wear and corrosion resistance, composition, hydrophilicity and surface roughness are known factors to affect osseointegrtaion process [15][16][17][18][19]. Among them, surface roughness seems to play an important role, while its optimization enhances hydrophilicity of the implant surface [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The laser-material interaction time is low at higher laser scanning speeds, and subsequently higher cooling rate and thermal gradient than the lower laser scanning speeds. Rapid solidification and cooling that occurred at high laser speed induced a higher microhardness value which agrees with reported data by Tavakoli et al (21).…”
Section: Microhardness Resultssupporting
confidence: 92%
“…Tafel plots in Figure 12 revealed that there are no pitting corrosion sites before and after the laser treatment (negative loop) during immersion of the laser-treated substrate in the salt solution. However, despite that, the laser treatment showed an additional improvement through the decrease in the value of the current density from 7.969*10 -7 to 3.969*10 -7 Amp which agree with (21). Furthermore, there is a noble shift of the curve if compared with untreated Ti.…”
Section: Chemical Corrosion Resultssupporting
confidence: 81%
“…The understanding of wetting of a surface by a liquid, leading to the spreading of those liquids over the surface, can be seen as a crucial factor that is adopted within surface chemistry and surface engineering including applications such as biomaterials [1][2][3] and coating technologies [4,5]. As demonstrated in current surface engineering literature, wettability characteristics of many materials can be altered by the means of laser-induced surface treatment [1,6,7] and other surface treatments [8][9][10]. Despite increased academic recognition and demand for greater industrial deployment, wetting and the effects of surface modification are still not fully understood within the engineering community.…”
Section: Introductionmentioning
confidence: 99%